Strategi Pengembangan Kredit Retel(Studi Pada Bank QNB Indonesia)2017 - Wenda Setia; Piter Abdulah (Sekolah Pascasarjana Perbanas Jakarta, 2018)
This study aims to formulate the strategy for developing retail credit at Bank QNB Indonesia. Analysis method using SWOT analysis. Assessment of internal and internal factors is done by distributing questionnaires. The results of the research are the identification of internal and external factors of the company, alternative strategies and priority strategies. The conclusion of this study is that banks have greater strengths than weaknesses and threats greater than the opportunities they have. The four alternative strategies of developing retail credit at QNB Bank Indonesia are: SO strategy by expanding retail credit distribution, using information technology to increase bank funding sources, expanding the network. WO strategy with competitive retail lending rates, credit priority for MSME sector. Strategy ST with the strengthening of handling of bad debts, improving the quality of human resources, and increasing the quality of services. WT strategy with accelerated credit application process and more careful credit policy. The main priority strategy is ST strategy. Suggestion of this research is company to always do analysis of external and internal factor so that company can apply appropriate strategy. Banks to implement SO strategies by enhancing marketing in both individual and MSME segments, enhancing m-banking capability so as to increase the amount of savings as a source of retail credit financing, and expanding the network by opening new branches and cooperating with cooperatives for retail credit distribution. In addition, further investigators can develop this research with other analytical tools. Keywords: Strategy, Retail Credit, SWOT.